Development of Indian Breakfast Foods with Coconut Flour - Ramaswamy, Lalitha; Sivagami, A. R (International Coconut Community Journal, 2011)
Coconut flour was incorporated in five Indian breakfast foods at 10%, 20% and 30% level by replacing the major cereal of each dish and organoleptically evaluated. Adai made with 10% incorporation had obtained the maximum scores, while those made with 20% and 30% were hard and rubbery. Uppuma made with 10% incorporation was almost equal to that of standard while the 30% incorporated one was unfit for consumption. Similarly mooli paratha made with 30% incorporation was crisp, however with 10% incorporation they were soft and acceptable. Vermicelli kichadi made with 30% incorporation was sticky, while the variation made with 10% was acceptable. Poories made with 10% incorporation were acceptable and the flavour was desirable due to the unique coconut flavour, however as the proportion of coconut flour increased the poories became crisper. Results of ANOVA show that there is a significant difference between the variations on account of coconut flour incorporation and with the standard. The fibre content of the most acceptable recipes was 4g more, while the carbohydrate and fat content were less than the standard which helps in combating disease conditions like obesity and diabetes mellitus. Therefore novel foods can be formulated with coconut flour and popularised.